2018
DOI: 10.3892/mmr.2018.8922
|View full text |Cite
|
Sign up to set email alerts
|

The role of VEGF in the diagnosis and treatment of malignant pleural effusion in patients with non‑small cell lung cancer (Review)

Abstract: Malignant pleural effusion (MPE) is a severe medical condition, which can result in breathlessness, pain, cachexia and reduced physical activity. It can occur in almost all types of malignant tumors; however, lung cancer is the most common cause of MPE, accounting for ~1/3 of clinical cases. Although there are numerous therapeutic approaches currently available for the treatment of MPE, none are fully effective and the majority can only alleviate the symptoms of the patients. Vascular endothelial growth factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
68
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(70 citation statements)
references
References 63 publications
0
68
0
2
Order By: Relevance
“…The effects of these can be divided into three categories: The first group of molecules stimulate the pleural inflammation (e.g., interleukin 2—IL2; tumor necrosis factor—TNF and interferon—INF); the second group of molecules stimulate tumor angiogenesis (e.g., angiopoietin 1 (ANG-1), angiopoietin 2 (AGN–2); the third group of molecules affect vascular hyperpermeability (e.g., vascular endothelial growth factor—VEGF, matrix metalloproteinases—MMP, chemokine (c-c motif) ligand 2—CCL, osteopontin—OPN, etc.) [1,19]. Additionally, studies show that mastocytes have a significant effect on MPE formation.…”
Section: Pleural Effusionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of these can be divided into three categories: The first group of molecules stimulate the pleural inflammation (e.g., interleukin 2—IL2; tumor necrosis factor—TNF and interferon—INF); the second group of molecules stimulate tumor angiogenesis (e.g., angiopoietin 1 (ANG-1), angiopoietin 2 (AGN–2); the third group of molecules affect vascular hyperpermeability (e.g., vascular endothelial growth factor—VEGF, matrix metalloproteinases—MMP, chemokine (c-c motif) ligand 2—CCL, osteopontin—OPN, etc.) [1,19]. Additionally, studies show that mastocytes have a significant effect on MPE formation.…”
Section: Pleural Effusionmentioning
confidence: 99%
“…In the last decade, researchers used genome analysis of tumor cells and discovered that tumors which have activating mutations EGFR , KRAS , PIK3CA , BRAF , MET , EML4/ALK and RET are connected to increased MPE formation [18,19,21]. KRAS mutations are common for distant metastases and EGFR mutations for tumors which metastasize via direct infiltration [18].…”
Section: Pleural Effusionmentioning
confidence: 99%
“…Marked elevation of VEGF was also reported in both malignant pleural effusion and malignant ascites, and considered to be a key molecule . Both malignant pleural effusion and malignant ascites were poor prognostic factor and resulted in decline of quality of life (QOL) . Bevacizumab combined with chemotherapy were reported to be a superior option for patients with both malignant pleural effusion and malignant ascites, and could improve patients' QOL .…”
Section: Discussionmentioning
confidence: 99%
“…Fucosterol can directly activate the Ras signaling pathway, PI3K-Akt signaling pathway, and ErbB signaling pathway, and indirectly activate the MAPK signaling pathway to regulate cell proliferation and apoptosis to achieve the therapeutic effect on NSCLC. From the perspective of the key signal transduction pathways( Figure 8B), it was found that both VEGF signaling pathway and ErbB signaling pathway can activate downstream signals to control angiogenesis, affect cell proliferation and migration, and play a crucial role in the development and metastasis of tumors [37][38][39]. Meanwhile, the PI3K-Akt signaling pathway participates in the regulation of cell cycle progression [40][41][42].…”
Section: Analysis Of An Integrated Pathway Mapmentioning
confidence: 99%